Strategic Management of Accreditation Improvement in Public Elementary Schools - Pratama, Fidya Arie; Khan, Habib Ur Rehman (Eduprof : Islamic Education Journal, 2025)
The implementation of accreditation should be in accordance with the new paradigm in the implementation of accreditation, which no longer differentiates between state and private institutions, utilizes community involvement and participation, and adheres to the principle of openness. The focus of this study is to obtain a role model for strategic management of accreditation held by public elementary schools. The research method used is a qualitative case study. The results of this study indicate the implementation of strategic management by improving teacher competence in the field of learning strategies in the classroom, in the implementation of independent curriculum, always learning independently and also learning together in the intra-school learning community. Involving stakeholders from all stakeholders, including teachers, students, parents, and the community is very important in supporting efforts to improve accreditation. The results of this study support the strategic management theory that emphasizes the importance of internal and external environmental analysis as a basis for strategic decision making. In the context of elementary school accreditation, data collection and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis have proven to be crucial initial steps in determining a comprehensive school quality improvement strategy.